Thermal behavior of asphalt pavement as an active solar collector under Malaysia climate condition using rubber tube - Beddu S.; Itam Z.B.; Ahmad M.; Alanimi F.B.I.; Zainoodin M. (Medwell Journals, 2023)
Malaysia has potential to generate alternative renewable solar energy. Rubber tube was embedded in asphalt pavement at a depth of 75 mm. Thermal behavior of solar heat was studied at different location in asphalt pavement. Asphalt pavement top surface which is exposed to the direct sunlight, temperature above the rubber tube, temperature of liquid (water) filled in rubber tube and temperature below the rubber tube were the locations chosen to observe the thermal behavior and heat transformation from top to bottom. The observation was carried out for 3 days in asphalt pavement and using thermodynamic first law to find the heat efficiency. Study concludes that the maximum surface temperature reach to 59.5C and water inside rubber tube temperature reach to 54.7C. In the result minimum 2.4% and maximum heat efficiency 22.7% produced by using rubber tube the case might be change using other metals. Medwell Journals, 2018.